2014
DOI: 10.1007/s13361-014-1048-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Structural Heterogeneity of an Intrinsically Disordered Protein Bound to a Partner by Combined ESI-IM-MS and Modeling

Abstract: Abstract. Intrinsically disordered proteins (IDPs) form biologically active complexes that can retain a high degree of conformational disorder, escaping structural characterization by conventional approaches. An example is offered by the complex between the intrinsically disordered N TAIL domain and the phosphoprotein X domain (P XD ) from measles virus (MeV). Here, distinct conformers of the complex are detected by electrospray ionization-mass spectrometry (ESI-MS) and ion mobility (IM) techniques yielding es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 76 publications
(105 reference statements)
3
41
0
Order By: Relevance
“…19 Overall, gas-phase methods appear uniquely suited to meet the challenge of describing the conformations and dynamics of flexible proteins as evidenced by the increasing number of publications in this area in recent years. [20][21][22][23][24] Nevertheless, recent studies describing the collapse of disordered structures in the absence of solvent have raised questions over the fidelity to which gas-phase methods can capture the solution conformations of these proteins. 25,26 Recent shifts in our understanding of how flexible species escape electrospray droplets during ESI also add to the complexity of describing the solution to gas-phase transfer of IDPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Overall, gas-phase methods appear uniquely suited to meet the challenge of describing the conformations and dynamics of flexible proteins as evidenced by the increasing number of publications in this area in recent years. [20][21][22][23][24] Nevertheless, recent studies describing the collapse of disordered structures in the absence of solvent have raised questions over the fidelity to which gas-phase methods can capture the solution conformations of these proteins. 25,26 Recent shifts in our understanding of how flexible species escape electrospray droplets during ESI also add to the complexity of describing the solution to gas-phase transfer of IDPs.…”
Section: Introductionmentioning
confidence: 99%
“…This ability of SAXS allows us to investigate the accuracy to which ESI charge state distributions represent the conformational space that is occupied by IDPs in solution. 24,[29][30][31][32] We find dramatically different structural depictions of the IDPs depending on the technique employed to characterize these proteins. In solution the IDP ensembles largely describe unimodal distributions of conformers whereas gas-phase methods describe a conformational space that is characterized by 3 distinct subpopulations broadly defined as compact (c), intermediate (i) and extended (e) with increasing Ω and charge.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note, however, that the range of complexes which can be studied by native MS methods is restricted to those that survive intact in the gas phase which, in turn, is determined by the nature of the non-covalent interactions involved in complex formation. For example, since hydrophobic interactions are weakened in the gas phase, macromolecular complexes that rely on hydrophobic contacts for assembly may not survive intact during the transfer to the gas phase [82,83]. In addition, the loss of a solvation shell may result in structural reorganization, as evidenced for water soluble proteins, including intrinsically disordered proteins or complexes with 'open' topologies as found in extended polyproteins, such as IgGs or ring-like subunit assemblies [76,81,163].…”
Section: Discussionmentioning
confidence: 99%
“…[90] with permission. may be too labile, and will not retain their native fold during nESI, although this is not always the case [82,83]. In the analysis of water soluble proteins using native MS, gentle ionization and instrument conditions are typically used to preserve non-covalent interactions [60].…”
Section: Introductionmentioning
confidence: 99%
“…In measles virus (a member of the Morbillivirus genus), the C-terminal region of phosphoprotein P is a globular domain of 49 amino acids, called X domain (XD), 2 composed of three ␣-helices organized as an anti-parallel bundle (12). Previous investigations on measles virus XD have suggested this domain to be structurally heterogeneous, populating at least two alternative conformations under native conditions (13). This feature is consistent with the findings of Kingston et al (14), who suggested that the native state of XD from mumps virus (a Rubulavirus member) represents an example of folding induced by crystal packing effects.…”
mentioning
confidence: 99%